IMPROVING THE SAFETY OF TRAINS WITH INCREASED WEIGHT AND LENGTH - Kravchuk, V. V.; Doronina, I. I.; Kharin, Ye. O. (Science and Transport Progress, 2007)
Based on the analysis of causes for damage of autocoupling devices in the trains of increased weight and lengths, the most probable reasons of train traffic safety disturbances have been shown. The ways of increasing the traffic safety and he causes of additional resistance to the train movement have been presented.